Multiobjective component sizing of a hybrid ethanol-electric vehicle propulsion system. (15th May 2020) - He, Yinglong; Wang, Chongming; Zhou, Quan; Li, Ji; Makridis, Michail; Williams, Huw; Lu, Guoxiang; Xu, Hongming
Highlights: An ethanol-gasoline blend model is incorporated into the PHEV powertrain simulation. The proposed method can provide market-oriented PHEV design solutions. Relationships among economic, energy and environment goals in PHEV design are studied. E25 PHEV can achieve energy saving (5.9%) and GHG emissions reduction (12.3%). Ethanol in E25 counts 13.8% of the total energy but only 4.8% of the GHG emissions. Abstract: Concerns over energy efficiency and greenhouse gas (GHG) emissions are driving research investments into advanced propulsion technologies. Plug-in hybrid electric vehicles (PHEVs) can provide a bridge that connects transport electrification to renewable bioenergy sources such as ethanol. However, it remains unclear how this pathway can simultaneously address economic, energy and environmental goals. To tackle this challenge, the present study explores, for the first time, the multiobjective optimal sizing of PHEVs powered by low-carbon sources of electricity and ethanol-gasoline blend. The empirical ethanol-gasoline blend model is incorporated into the PHEV simulation whose relevant parameters are validated using laboratory data from the European Commission – Joint Research Centre. We develop a full picture of the use-phase well-to-wheel (WTW) GHG emissions from ethanol, gasoline and grid electricity and their energy consumptions. Consequently, market-oriented PHEV sizing solutions are provided as per the power utility generation portfolio and automobile fuel properties of the target region. The results indicate that better performances of the PHEV, regarding GHG emissions and energy consumption, are associated with larger battery size and smaller engine displacement but result in a higher cost-to-power ratio. Specifically, for E25-fuelled PHEVs in markets with world average electricity carbon intensity, every 1.0 USD/kW increase in cost-to-power ratio leads to savings of 1.6 MJ energy consumption and 1.7 g CO2 -eq/km WTW GHG emissions. Moreover, a clear benefit of using E25 in the hybrid propulsion system is identified, where the energy consumption and GHG emissions can be reduced by 5.9% and 12.3%, respectively.